2016
DOI: 10.1002/ddr.21343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intranasal Oxytocin on Long‐Term Memory in Healthy Humans: A Systematic Review

Abstract: Neuropeptide oxytocin is implicated in complex emotional and social behavior and it appears to play an important role in learning and memory. Animal studies have shown that the effects of exogenous oxytocin on memory vary according to the timing of administration, context, gender and dose and it may improve the memory of social, but not non-social stimuli. Oxytocin is intricately involved in a broad array of neuropsychiatric functions and may therefore be a pharmacological target for several psychiatric disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…N2B drug delivery is of increasing interest since it was demonstrated that tracers like wheat-germ agglutinin-HRP conjugates could be found in the axonal projections of olfactory sensory neurons and in the olfactory bulb [ 36 ]. As clinical studies with intranasally delivered CNS-active peptides and small proteins are ongoing, the delivery of larger proteins via the nasal pathway as an alternative to bypass the BBB becomes more and more attractive [ 13 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N2B drug delivery is of increasing interest since it was demonstrated that tracers like wheat-germ agglutinin-HRP conjugates could be found in the axonal projections of olfactory sensory neurons and in the olfactory bulb [ 36 ]. As clinical studies with intranasally delivered CNS-active peptides and small proteins are ongoing, the delivery of larger proteins via the nasal pathway as an alternative to bypass the BBB becomes more and more attractive [ 13 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of the intranasal route are the minimally-invasive administration, reduced systemic side effects due to direct CNS targeting, and improved patient compliance compared to intrathecal delivery [ 6 , 7 ]. As the feasibility of nose to brain (N2B) drug delivery was already shown for sumatriptan, oxytocin, insulin, and some other drugs, it is of particular interest to investigate whether the N2B route is also suitable for proteins with a higher molecular weight such as antibodies [ 7 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in oxytocin appear to be associated with psychiatric conditions involving deficits in social behavior including autism spectrum disorders and schizophrenia ( 84 86 ). Although findings in the literature lack consistency, recent research on both central and peripheral actions of oxytocin have identified potential relationships with mood and anxiety ( 87 ), learning and memory ( 88 ), improvement of wound healing ( 89 ), modulation of inflammatory responses ( 90 , 91 ), neuroprotection ( 89 , 91 , 92 ), regulation of food intake and body weight ( 93 ), and reduction of pain sensitivity ( 94 , 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, OXT versus placebo treatment effects are assessed on specific behavioral tasks or on brain activity patterns in either a within-subject or a group design, which have been extensively reviewed elsewhere [1,15,[137][138][139]. Thus, substantial effects of IN OXT were described on social cognition [138,[140][141][142], fear [143,144], empathy [145,146], trust [147], and even xenophobia [148,149] often accompanied by altered neuronal activity [150].…”
Section: Translational Perspectivesmentioning
confidence: 99%